Synthesis of bio-hydrocarbons pentadecane from crude palm oil (CPO) using recombinant E.coli produced fatty acid photodecarboxylase From Chlorella variabilis - Irma kresnawaty; Farhan Palgunadi; Yora Faramitha; Kenny Lischer; Ayu Rahayu Saraswanti; Fauziatul Fitriyah; Djoko Santoso (Menara Perkebunan)
Exploration of natural resources, particularly fossil fuels, is necessary given the sharp rise in energy demand across a wide range of industries. The risk of unpredictable fuel costs, rising pollution, and climate change is elevated as a result of that specific event. In order to address the problem of danger originating from present conventional fuel, it is crucial to use renewable energy that is regarded as sustainable and safe. In the future, bio-hydrocarbons are one energy source that is expected to be used as fuel. In both biological and non-biological processes, biohydrocarbons—hydrocarbons originating from biomass—can be created. Employing the Chlorella variabilis Fatty Acid Photodecarboxylase (CvFAP) enzyme from E. coli recombinant is a remarkable recent technique for producing bio-hydrocarbons. This enzyme has the ability to change free fatty acids, according to extensive studies when induced by blue light and accompanied by the addition of substrates. This study has confirmed the success of producing bio-hydrocarbons in the form of pentadecane with a selectivity of 16.44%. This experiment also indicated that several substantial components are needed in the bio-hydrocarbon synthesis process to obtain an optimal result. The components are the use of TB growth media, the selection of a protein concentration of 1777.5 l ppm, activation time for 3 hours, and the preference for substrate type in the form of 50% CPO.